Adaptive Control for Improved Virtual Synchronous Generator Under Imbalanced Grid Voltage - Yangyang Chen; Wei Han; Youhao Hu; Yilin Zhang (IEEE Open Journal of the Industrial Electronics Society)
As renewable energy continues to grow, more inverter-based distributed generators are being integrated into power grids, in which virtual synchronous generator (VSG) is widely adopted to regulate system voltage and stabilize frequency. However, grid voltage imbalances can cause serious oscillations in active power and system frequency, thus severely limiting the effectiveness of VSGs. Consequently, this study proposes an adaptive control strategy to enhance the dynamic performance of VSG under an imbalanced grid voltage. Compared to conventional VSG control methods, the proposed approach enables dynamic adjustment of the inertia and damping coefficients based on the output angular frequency oscillations, so as to shorten the settling time and reduce active power overshoot. The error-driven adaptive mechanism forms a closed-loop control, which effectively keeps the system stable regardless of parameter variations. Additionally, it combines with balanced output current (BOC), constant active power (CAP), and constant reactive power (CRP) control modes to further improve effectiveness. Finally, verifications have been conducted in the MATLAB/SIMULINK and hardware-in-the-loop (HIL) environment to demonstrate the superiority and feasibility of the proposed method.